Goya´s Whims. An Facial Expression Analysis Of Engraving # 44. - N., López-Valverde; A., López-Valverde (Advances in Social Sciences Research Journal, 2018)
Francisco de Goya y Lucientes (1746-1828) a Spanish painter and engraver, has been one of the most relevant artists both in Spain and universally. Two of his most famous engravings, masterpieces housed in the Prado Museum in Madrid, are “La Maja Desnuda” (“The lady without clothes”) and “La Maja Vestida” (“The lady with clothes”), and the portrait of the royal family entitled “The Family of Carlos V”. The invasion of Spain by Napoleonic forces was captured in two masterpieces: “The charge of the Mameluks” and “The shootings at the Príncipe Pío hill” (Third of May). Within his artistic production, there was a commercial vein -his work was done to order- and a more analytical and critical element, in which the series entitled “Los Caprichos” can be framed, where, with deep irony, he satirizes the social vices and superstitions of the period. This latter aspect of his work, means that Goya can be considered a philosophical and physiognomic artist, reflecting the most sinister and sinful aspects of human beings, in the faces and expressions of his subjects.